Identification of a promiscuous T-cell epitope in Mycobacterium tuberculosis Mce proteins - Panigada, Maddalena; Sturniolo, Tiziana; Besozzi, Giorgio; Boccieri, Maria Giovanna; Sinigaglia, Francesco; Grassi, Giuliana Gialdroni; Grassi, Fabio (Infection and immunity, 2002)
The characterization of Mycobacterium tuberculosis antigens inducing CD4(+) T-cell responses could critically contribute to the development of subunit vaccines for M. tuberculosis. Here we performed computational analysis by using T-cell epitope prediction software (known as TEPITOPE) to predict promiscuous HLA-DR ligands in the products of the mce genes of M. tuberculosis. The analysis of the proliferative responses of CD4(+) T cells from patients with pulmonary tuberculosis to selected peptides displaying promiscuous binding to HLA-DR in vitro led us to the identification of a peptide that induced proliferation of CD4(+) cells from 50% of the tested subjects. This study demonstrates that a systematic computational approach can be used to identify T-cell epitopes in proteins expressed by an intracellular pathogen.